Kesiapan Guru Bahasa Indonesia dalam Melaksanakan Kurikulum Merdeka di SMP Negeri Kota Bengkulu - Allya Try Sukma Dewy; Muhammad Arifin; Didi Yulistio (UNIB Press, 2026)
The purpose of this study was to determine the Readiness of Indonesian Language Teachers in implementing the Merdeka Curriculum in State Junior High Schools in Bengkulu City. This research uses a descriptive method with a quantitative approach. The population used in this study were all Indonesian language teachers in Bengkulu City State Junior High Schools, totaling 129 people. The sample in this study which was taken using purposive sampling technique was 30 Indonesian language teachers, namely at SMPN 5 Bengkulu City, SMPN 8 Bengkulu City, SMPN 14 Bengkulu City, SMPN 18 Bengkulu City and SMPN 17 Bengkulu City. The data collection technique used was questionnaire technique. The readiness of Indonesian language teachers in implementing the Merdeka Curriculum is assessed from three aspects, namely, planning, implementation and evaluation. The data analysis technique used in this research is descriptive data analysis technique and calculating the average. The results of the study can be stated that in general it shows that Indonesian language teachers are ready with an average of 4.19 because they are in the average range of 3.4-4.1. The results specifically that (1) Indonesian language teacher readiness in the aspect of lesson planning with an average value (4.4) including the category very ready (2) Indonesian language teacher readiness in the aspect of lesson implementation with an average value (4.1) including the category ready and (3) Indonesian language teacher readiness in the aspect of evaluation with an average value (4.2) including the category very ready.